#### jasongousis72

##### New member

- Joined
- Sep 16, 2021

- Messages
- 1

x10^x/11^x>=(x+1)10^(x+1)/11^(x+1)

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter jasongousis72
- Start date

- Joined
- Sep 16, 2021

- Messages
- 1

x10^x/11^x>=(x+1)10^(x+1)/11^(x+1)

- Joined
- Oct 6, 2005

- Messages
- 10,633

Welcome to our tutoring boards! :) This page summarizes some main points from our posting guidelines. As our name implies, we provide math help (primarily to students with homework). We do not generally post immediate answers or step-by-step solutions. We prefer to help by having a...

www.freemathhelp.com

Please share with us how far you get. Can you say what part you find confusing? Thanks.

- Joined
- Jan 27, 2012

- Messages
- 7,770

- Joined
- Dec 30, 2014

- Messages
- 11,455

So x*x^10/x^11 = x^11/x^11 = 1.

Now (x+1)^10*(x+1) = [(x+1)*(x+1)*(x+1)*(x+1)*(x+1)*(x+1)*(x+1)*(x+1)*(x+1)*(x+1)]*(x+1) = (x+1)*(x+1)*(x+1)*(x+1)*(x+1)*(x+1)*(x+1)*(x+1)*(x+1)*(x+1)*(x+1) = (x+1)^11

So, (x+1)^10*(x+1)/(x+1)^11 = (x+1)^11/(x+1)^11 =1

For which values of x are both sides equal to one another? Hint: both sides always equal 1.

- Joined
- Jan 27, 2012

- Messages
- 7,770

Uh- What I see is NOT "x^10" but "10^x"!

- Joined
- Jan 27, 2012

- Messages
- 7,770

Divide both sides by 10^x to getx10^x/11^x>=(x+1)10^(x+1)/11^(x+1)

x/11^x>= 10(x+1)/11^(x+1)

Multiply both sides by 11^(x+1) to get

11x>= 10(x+ 1)

Distribute the 10 on the right

11x>= 10x+ 10

Subtract 10x from both sides of the equation

x>= 10.